Profile of Students’ Conceptual Understanding of Physics in Senior High School - Khoiri, Nur; Ristanto, Sigit; Kurniawan, Affandi Faisal (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2022)
This research aimed to identify the profile of physical concept mastery of Senior High School/Aliyah School students in Semarang as a result of the transition from offline to online learning. The research employed the descriptive quantitative approach in which the tests and questionnaires were used to collect data. The school type (Senior High School/Aliyah School), school ownership (Private/State), and student’s interest in learning are all considered in the profile analysis. This study was carried out in Semarang, Indonesia, with a sample of 250 students from MAN 2 Semarang, SMA Negeri 1 Semarang, and SMA Negeri 9 Semarang. The findings revealed: 1) The percentage of students with concept mastery scores with the highest answer being questioned was 12 (88.2%). The results showed: 1) The percentage of students with concept mastery scores that really the highest answer lies in question 12 with a percentage of 88.2% on fluid material (Bernoulli’s Law) with a cognitive level of C2. While the percentage value of the student’s mastery of concepts which is the lowest, lies in questions number 3 (Uniform Speed and Uniform Acceleration subject matter) and 4 (moment of inertia/center of gravity and rigid body balance subject matter) with a percentage of 57% each with successive levels of cognition, C3 and C4, 2) Following tutoring is not effective because it does not affect physical learning achievement, and 3) there is a positive (unidirectional) significant (mean) relationship between independence and learning motivation on physical learning achievement. The results of this study can be used as a reference for researchers, educational policymakers, and stakeholders related to the handling of post-pandemic education.